Resin sheet and laminate
The urethane-acrylic composite resin sheet addresses the challenge of sealing electronic circuit boards by providing flexibility and heat resistance through a microphase-separated structure, ensuring effective coverage and protection against environmental stress.
Patent Information
- Application Number
- JP2020194273
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-24
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2040-11-24
AI Technical Summary
Existing methods for sealing electronic circuit boards with epoxy resin face challenges in achieving both flexibility and heat resistance, leading to issues such as peeling, cracking, and short circuits due to insufficient crosslinking and brittle coatings.
A resin sheet composed of a urethane-acrylic composite resin, containing urethane units and crystalline (meth)acrylic units, which form a microphase-separated structure for excellent coverage and flexibility, and crosslinking to provide heat resistance.
The resin sheet achieves excellent coverage of uneven parts, high flexibility, and heat resistance, allowing for easy sealing of electronic circuit boards at low temperatures and in a short time, while maintaining adhesion and preventing equipment malfunctions.
Smart Images

Figure 0007613064000001 
Figure 0007613064000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin sheet and a laminate having excellent covering ability for uneven portions, high flexibility and heat resistance. [Background technology]
[0002] In recent years, a large number of electronic control technologies have been adopted in vehicles to assist driving and improve fuel efficiency, and as a result, electronic control units have become larger and the number of units installed has increased. This has resulted in issues such as increased vehicle weight and a lack of installation space, and there is a demand for smaller electronic control units.
[0003] On the other hand, electronic circuit boards equipped with electronic components such as IC chips mounted on electronic control units are generally sealed with sealing resin to protect the board from changes in the external environment such as water and dust. Various sealing methods have been used so far, such as potting, dipping, coating, and spraying, but these methods have the problem that they require thick coating and make it difficult to sufficiently miniaturize. Even if the sealing layer can be made thinner, there are problems such as material loss and long process times due to complicated work.
[0004] To address these issues, for example, Patent Documents 1 and 2 propose a method in which a resin sheet consisting of an epoxy resin, a curing agent, an inorganic filler, and a flame retardant is softened by heat under its own weight to cover the irregularities of electronic components, and then cured in that state to form an encapsulating film.
[0005] However, although these methods can simplify the sealing process of electronic circuit boards, when inorganic fillers are highly filled to suppress fluidity, crosslinking is insufficient and heat resistance is lost, and when the amount of inorganic filler is reduced, the fluidity of the epoxy resin is too high and the resin cannot sufficiently cover the protrusions, making it difficult to achieve both fluidity and heat resistance. In addition, since the coating film after curing is hard and brittle, repeated heat cycles may cause peeling from the board and cracks, or excess stress may be applied to the board, electronic components, and solder joints, causing short circuits, disconnections, current leakage, etc., which may lead to malfunction of the device. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2011-246596 A [Patent Document 2] JP 2012-054363 A Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a resin sheet which has excellent covering ability for uneven parts, high flexibility and heat resistance, and can easily seal electronic circuit boards. [Means for solving the problem]
[0008] As a result of intensive research, the present inventors have found that a resin sheet formed from a resin composition containing a urethane-acrylic composite resin having a constituent unit derived from a crystalline (meth)acrylic monomer and a constituent unit derived from a (meth)acrylic monomer having a crosslinkable group, and a crosslinking agent, can solve the above-mentioned problems.
[0009] A resin sheet according to one embodiment of the present invention is a resin sheet formed from a resin composition containing a urethane-acrylic composite resin and a crosslinking agent, wherein the urethane-acrylic composite resin is a resin formed by linking a urethane unit (A) and a (meth)acrylic unit (B) via a chain transfer agent residue, and the (meth)acrylic unit (B) has a constituent unit derived from a crystalline (meth)acrylic monomer (b1) and a constituent unit derived from a (meth)acrylic monomer (b2) having a crosslinkable group (excluding the constituent unit derived from (b1)).
[0010] A resin sheet according to another embodiment of the present invention is characterized in that the crystalline (meth)acrylic monomer (b1) is a (meth)acrylate having a linear alkyl group having 16 or more carbon atoms.
[0011] A resin sheet according to another embodiment of the present invention is characterized in that the urethane-acrylic composite resin contains urethane units (A) in a range of 30 to 70 mass % based on the mass of the urethane-acrylic composite resin.
[0012] A resin sheet according to another aspect of the present invention is used for sealing an electronic device.
[0013] A laminate according to another aspect of the present invention comprises the above-mentioned resin sheet and a release material. Effect of the Invention
[0014] The present invention can provide a resin sheet that has excellent coverage of uneven parts, high flexibility and heat resistance, and can easily seal electronic circuit boards at low temperature in a short time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] <Resin sheet> The resin sheet of the present invention is formed from a resin composition containing a urethane-acrylic composite resin in which a urethane unit (A) and a (meth)acrylic unit (B) are linked by a chain transfer agent residue, and a crosslinking agent, and is characterized in that the (meth)acrylic unit (B) has a constituent unit derived from a crystalline (meth)acrylic monomer (b1) and a constituent unit derived from a (meth)acrylic monomer (b2) having a crosslinkable group (excluding the constituent unit derived from (b1)). By adopting such a configuration, the flexible urethane portion and the acrylic portion having self-assembly properties form a microphase separation structure, and even before curing, the resin sheet maintains a solid shape at room temperature due to the crystallization effect of the crystalline (meth)acrylic monomer (b1). On the other hand, at a relatively low temperature 20 to 40°C higher than the crystallization temperature of the crystalline (meth)acrylic monomer (b1), the resin sheet softens due to the elimination of the crystallization effect while maintaining a certain cohesive force due to the cohesive force derived from the urethane unit (A), and quickly follows the unevenness. After crosslinking, the resin sheet exhibits excellent extensibility and adhesion due to the urethane portion, and excellent heat resistance due to the crosslinked structure of the acrylic portion. As a result, the resin sheet of the present invention can exhibit excellent coverage of uneven portions and high flexibility and heat resistance under low-temperature conditions of about 80°C for 1 minute for a short time. Therefore, the resin sheet of the present invention is suitable for use in protecting various electronic circuit boards, that is, various boards such as rigid boards and FPC boards. In this specification, the term "chain transfer agent residue" refers to a partial structure of a composite resin that can be identified as being derived from a chain transfer agent, and "crystalline" refers to a melting point in the range of 30 to 100°C, and a clear endothermic peak rather than a stepwise endothermic change in differential scanning calorimetry (DSC).
[0016] <Urethane-acrylic composite resin> The urethane-acrylic composite resin in the present invention may have a structure in which a urethane unit (A) and a (meth)acrylic unit (B) having a constituent unit derived from a crystalline (meth)acrylic monomer (b1) and a constituent unit derived from a (meth)acrylic monomer (b2) having a crosslinkable group (excluding the constituent unit derived from (b1)) are linked together via a chain transfer agent residue, and the method for producing the resin is not limited, but it can be preferably produced by the following method. First, a urethane prepolymer having isocyanato groups at both ends is formed by reacting a polyol with a polyisocyanate (hereinafter, step 1). Next, a chain transfer agent is added to synthesize a urethane unit (A) having chain transfer agent residues at both ends of the urethane prepolymer (hereinafter, step 2). Thereafter, the chain transfer agent residue contained in the obtained urethane unit (A) is used to chain transfer polymerize an ethylenically unsaturated monomer including a constituent unit derived from a crystalline (meth)acrylic monomer (b1) and a constituent unit derived from a (meth)acrylic monomer (b2) having a crosslinkable group (excluding the constituent unit derived from (b1)), to form an ethylenically unsaturated monomer polymer unit (B) (hereinafter, step 3). In this manner, a urethane-acrylic composite resin can be obtained in which the urethane unit (A) and the polymer unit (B) of an ethylenically unsaturated monomer are linked together via a chain transfer agent residue. All of these reactions may be carried out with or without a solvent, and when a solvent is used, the solvent may be removed under reduced pressure or at normal pressure during or after the reaction.
[0017] <Urethane unit (A)> First, the urethane unit (A) of the urethane-acrylic composite resin will be described below. The urethane-acrylic composite resin of the present invention can be formed by reacting polyol with polyisocyanate in a solvent or without a solvent. The urethane unit is flexible and has excellent adhesion to substrates, so it can exhibit excellent coating properties.
[0018] [Polyol] Examples of the polyol constituting the urethane unit (A) include polyether polyols, polyester polyols, polycarbonate polyols, polyolefin polyols, vegetable oil-based polyols, other polyols including acrylic polyols, and complexes thereof. These polyols may be used alone or in combination of two or more.
[0019] (Polyether polyol) The polyether polyol may be any compound having two or more hydroxyl groups and two or more ether bonds in the molecule, and examples thereof include polymers or copolymers of methylene oxide, ethylene oxide, propylene oxide, tetrahydrofuran, and the like, and specific examples thereof include polyethylene glycol, polypropylene glycol, poly(ethylene / propylene) glycol, and polytetramethylene glycol. Examples of the polyether polyol include polyether polyols obtained by condensation of hexanediol, methylhexanediol, heptanediol, octanediol, or mixtures thereof.
[0020] Further examples of polyether polyols include polyols obtained by adding an alkylene oxide, such as methylene oxide, ethylene oxide, propylene oxide, butylene oxide, tetrahydrofuran, or polyoxytetramethylene oxide, to a starting material that is a compound having at least two active hydrogen groups, such as a low molecular weight polyol, an aliphatic amine compound, an aromatic amine compound, an alkanolamine, or a bisphenol.
[0021] Among the above compounds having two or more active hydrogen groups, examples of the low molecular weight polyol include difunctional low molecular weight polyols and trifunctional or higher functional low molecular weight polyols.
[0022] Examples of the bifunctional low molecular weight polyols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, pentanediol, hexanediol, octanediol, nonanediol, dipropylene glycol, diethylene glycol, triethylene glycol, 3-methyl-1,5-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, and the like. Examples of suitable hydroxyalkyl groups include dimethylol, polyoxyethylene glycol (10 or less moles added), polyoxypropylene glycol (10 or less moles added), cyclohexanediol, cyclohexanedimethanol, tricyclodecane dimethanol, cyclopentadiene dimethanol, dimer diol, bisphenol B, N,N-bis(2-hydroxypropyl)aniline, dimethylolacetic acid, dimethylolpropionic acid, dimethylolbutanoic acid, 2,2-dimethylolbutyric acid, 2,2-dimethylolpentanoic acid, dihydroxysuccinic acid, dihydroxypropionic acid, and dihydroxybenzoic acid.
[0023] Examples of the trifunctional low molecular weight polyols include trimethylolethane, trimethylolpropane, 1,1,1-trimethylolbutane, 1,2,3-butanetriol, 1,2,4-butanetriol, 1,2,6-butanetriol, trimethylolbutene, trimethylolpentene, trimethylolhexene, trimethylolheptene, trimethyloloctene, trimethylolnonene, trimethyloldecene, trimethylolundecene, trimethyloldodecene, trimethyloltridecene, trimethylol Trimethylolpentadecene, Trimethylolhexadecene, Trimetrolheptadecene, Trimethyloloctadecene, 1,1,1-trimethylol-2-methyl-hexane, 1,1,1-trimethylol-3-methyl-hexane, 1,1,1-trimethylol-2-ethyl-hexane, 1,1,1-trimethylol-3-ethyl-hexane, Trimethylolhexene, 1,2,3-octanetriol, 1,3,7-octanetriol, 3,7-dimethyl-1,2,3-octanetriol, 1,1,1-, 1,1,1- Trimethylol decane, 1,2,10-decanetriol, 1,1,1-trimethylol isoheptadecane, 1,1,1-trimethylol-seA-butane, 1,1,1-trimethylol-tert-pentane, 1,1,1-trimethylol-tert-nonane, 1,1,1-trimethylol-tert-tridecane, 1,1,1-trimethylol-tert-heptadecane, 1,1,1-trimethylol-2-methyl-hexane, 1,1,1-trimethylol-3-methyl-hexane, 1,1,1-trimethylol -2-ethyl-hexane, 1,1,1-trimethylol-3-ethyl-hexane, 1,1,1-trimethylol isoheptadecane, 1,2,3,4-butanetetraol, pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, diglycerin, triglycerin, polyglycerin, ditrimethylolethane, ditrimethylolpropane, tris(2-hydroxyethyl)isocyanurate, benzene-1,3,5-triol, benzene-1,2,3-triol, stilbene-3,Examples of sucrose, 4',5-triol, sucrose, inositol, sorbitan, sorbitol, mannitol, saccharose, cellulose, and xylitol.
[0024] Among the compounds having two or more active hydrogen groups, examples of the aliphatic amine compounds include ethylenediamine, isophoronediamine, triethylenetetramine, diethylenetriamine, and triaminopropane. Examples of the aromatic amine compounds include toluenediamine and diphenylmethane-4,4-diamine. Examples of the alkanolamine compounds include ethanolamine and diethanolamine. Examples of the bisphenol compounds include bisphenol B, bisphenol BP, bisphenol C, bisphenol A, bisphenol E, and bisphenol F.
[0025] (Polyester polyol) The polyester polyol may be, for example, a polyester polyol obtained by condensation reaction of the above-mentioned low molecular weight polyol with a dibasic acid component.
[0026] Examples of the dibasic acid component include aliphatic or aromatic dibasic acids such as terephthalic acid, adipic acid, azelaic acid, sebacic acid, dimer acid, hydrogenated dimer acid, phthalic anhydride, isophthalic acid, trimellitic acid, glutaric acid, pimelic acid, suberic acid, and sebacic acid, and their anhydrides.
[0027] Examples of the polyester polyol include polyester polyols obtained by ring-opening polymerization of cyclic ester compounds such as lactones, such as ε-caprolactone, poly(β-methyl-γ-valerolactone), and polyvalerolactone.
[0028] (Polycarbonate polyol) Examples of the polycarbonate polyol include reaction products of the above-mentioned low molecular weight polyols and carbonate compounds such as dialkyl carbonates, alkylene carbonates, and diaryl carbonates. The dialkyl carbonate may be dimethyl carbonate, diethyl carbonate, etc. The alkylene carbonate may be ethylene carbonate, etc. The diaryl carbonate may be diphenyl carbonate, etc.
[0029] (Polyolefin polyol) Examples of polyolefin polyols include hydroxyl-containing polybutadiene, hydrogenated hydroxyl-containing polybutadiene, hydroxyl-containing polyisoprene, hydrogenated hydroxyl-containing polyisoprene, hydroxyl-containing chlorinated polypropylene, and hydroxyl-containing chlorinated polyethylene.
[0030] (Vegetable oil-based polyol) Examples of vegetable oil-based polyols include polyols made from castor oil, dimer acid, or soybean oil, which are derived from plants.
[0031] The number average molecular weight of these polyols is preferably 500 or more and less than 5,000, and more preferably 700 or more and less than 3,500.
[0032] Furthermore, for the purpose of adjusting the urethane bond concentration and introducing various functional groups, the above-mentioned low molecular weight polyols, aliphatic amine compounds, and aromatic amine compounds can be used in combination.
[0033] [Polyisocyanate] Examples of the polyisocyanate constituting the urethane unit (A) include aromatic, aliphatic, and alicyclic polyisocyanates. These may be used alone or in combination of two or more.
[0034] Examples of aromatic polyisocyanates include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, tolidine diisocyanate, xylylene diisocyanate, m-tetramethylxylene diisocyanate, p-tetramethylxylene diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 3,3'-dimethoxy-4,4'-biphenylene diisocyanate, 3,3'-dichloro-4,4'-biphenylene diisocyanate, and 1,5-tetrahydronaphthalene diisocyanate.
[0035] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, lysine ester triisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate tetramethylene diisocyanate, pentamethylene diisocyanate, and trimethylhexamethylene diisocyanate.
[0036] Examples of alicyclic polyisocyanates include isophorone diisocyanate, 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,4-bis(isocyanatemethyl)cyclohexane, hydrogenated xylylene diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate.
[0037] The reaction between polyol and polyisocyanate can be carried out preferably in the absence of a solvent using a known urethane reaction, and by using an excess of polyisocyanate, a urethane prepolymer having isocyanato groups at both ends can be obtained. The molar ratio of isocyanato groups to hydroxyl groups (NCO moles / OH moles) during the reaction is preferably 1.05 to 2.00, more preferably 1.10 to 1.50. In the urethanization reaction, a catalyst may be used for the purpose of adjusting the reactivity.
[0038] As the catalyst, known metal catalysts, amine catalysts, etc. can be used. As the metal catalyst, for example, dibutyltin dilaurate, tin octoate, dibutyltin di(2-ethylhexoate), 2-ethylhexoate lead, 2-ethylhexyl titanate, titanium ethyl acetate, 2-ethylhexoate iron, 2-ethylhexoate cobalt, zinc naphthenate, cobalt naphthenate, and tetra-n-butyltin can be mentioned. As the amine catalyst, for example, tertiary amines such as tetramethylbutanediamine can be mentioned. The amount of the catalyst to be added is preferably in the range of 0.05 to 1 mol% based on the mass of the polyol.
[0039] <Chain transfer agent> The chain transfer agent in the present invention is not particularly limited, but is preferably a chain transfer agent having a sulfanyl group. As the chain transfer agent having a sulfanyl group, one having a functional group capable of reacting with an isocyanato group and a sulfanyl group in the molecule is preferably used. When the chain transfer agent is used, the terminal isocyanato group in the urethane prepolymer reacts with the functional group capable of reacting with an isocyanato group in the chain transfer agent, and a urethane unit (A) having a sulfanyl group at both ends can be formed. The chain transfer agent can be used alone or in combination of two or more of known chain transfer agents.
[0040] The functional group capable of reacting with the isocyanato group includes a hydroxyl group or an amino group, and from the viewpoint of reactivity, an amino group is preferable. Since an amino group is more reactive than a sulfanyl group, it reacts preferentially with the terminal isocyanato group of the urethane prepolymer to form a urea bond, and can efficiently introduce a sulfanyl group into the terminal of the urethane unit (A). As such a chain transfer agent, a compound having one amino group and one sulfanyl group in the molecule is more preferable.
[0041] Examples of compounds having one amino group and one sulfanyl group in the molecule include aminoalkanethiols such as 2-aminoethanethiol, 3-aminopropyl-1-thiol, 1-aminopropyl-2-thiol, and 4-amino-1-butanethiol; and aminobenzenethiols such as 2-aminothiophenol, 3-aminothiophenol, and 4-aminothiophenol. Among these, preferred are aminoalkanethiols, and more preferred is 2-aminoethanethiol.
[0042] [Urethane unit (A) content] The urethane-acrylic composite resin in the present invention contains the urethane unit (A) in a range of preferably 30 to 70% by mass, more preferably 35 to 65% by mass, based on the mass of the urethane-acrylic composite resin. When the content of the urethane unit (A) is 30 to 70% by mass, it is preferable because the unevenness covering property and the flexibility and heat resistance of the cured film are excellent.
[0043] The weight average molecular weight of the urethane unit (A) is not particularly limited, and is preferably in the range of 3,000 to 200,000. When it is 3,000 or more, excellent adhesive strength is obtained, and when it is 200,000 or less, adjustment of viscosity becomes easy.
[0044] <(Meth)acrylic unit (B)> The (meth)acrylic unit (B) in the present invention has a structural unit derived from a crystalline (meth)acrylic monomer (b1) and a structural unit derived from a (meth)acrylic monomer (b2) having a crosslinkable group (excluding the structural unit derived from (b1)), and is specifically a polymer of an ethylenically unsaturated monomer containing a crystalline (meth)acrylic monomer (b1) and a (meth)acrylic monomer (b2) having a crosslinkable group (excluding (b1)). Specifically, the urethane unit (A) having a chain transfer agent residue at both ends obtained in step 2, and an ethylenically unsaturated monomer containing a crystalline (meth)acrylic monomer (b1) and a (meth)acrylic monomer (b2) having a crosslinkable group (excluding (b1)) are polymerized in the presence of a polymerization initiator to obtain a urethane-acrylic composite resin, which is a block polymer in which the urethane unit (A) and the (meth)acrylic unit (B) are linked by a chain transfer agent residue.
[0045] The (meth)acrylic unit (B) crystallizes at room temperature due to the structural unit derived from the crystalline (meth)acrylic monomer (b1), increasing the cohesive force of the urethane-acrylic composite resin, allowing it to maintain its sheet shape even when uncured. On the other hand, when the crystallization temperature is exceeded, the cohesive force is immediately eliminated, the resin sheet softens, and forms a film that conforms to the unevenness of the electronic circuit board. Furthermore, by crosslinking the (meth)acrylic unit (B) with a crosslinking agent, the resulting cured film becomes a tough film with waterproof, stain-resistant, and heat-resistant properties, making it possible to seal the electronic circuit board.
[0046] [Crystalline (meth)acrylic monomer (b1)] The crystalline (meth)acrylic monomer is not particularly limited as long as it is a (meth)acrylic monomer having the above-mentioned "crystallinity", and for example, a (meth)acrylate having a linear alkyl group having 16 or more carbon atoms can be used. Examples of such (meth)acrylates having a linear alkyl group having 16 or more carbon atoms include cetyl (meth)acrylate, stearyl (meth)acrylate, eicosyl (meth)acrylate, and behenyl (meth)acrylate. From the viewpoint of crystallinity, those having a linear alkyl group having 18 or more carbon atoms are preferable.
[0047] [Content of crystalline (meth)acrylic monomer (b1)] The content of the crystalline (meth)acrylic monomer (b1) is preferably in the range of 50 to 95 mass%, more preferably in the range of 55 to 90 mass%, based on the total mass of the monomers constituting the (meth)acrylic unit (B). When the content of the crystalline (meth)acrylic monomer (b1) is 50 mass% or more, the unevenness covering ability is excellent, and when it is 95 mass% or less, the flexibility and heat resistance of the cured film are excellent.
[0048] [(Meth)acrylic monomer (b2) having a crosslinkable group (excluding (b1)] The (meth)acrylic monomer (b2) having a crosslinkable group is not particularly limited as long as it has a crosslinkable group in the molecule that can react with a crosslinking agent described below. Examples of such crosslinkable groups include a hydroxyl group, an epoxy group, a carboxyl group, an isocyanato group, and blocked forms thereof.
[0049] Examples of the (meth)acrylic monomer having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-3-allyloxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, or caprolactone adducts of these monomers (number of moles added: 1 to 5), polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, and glycerin mono(meth)acrylate.
[0050] Examples of the (meth)acrylic monomer having an epoxy group include glycidyl (meth)acrylate, 3,4-epoxybutyl (meth)acrylate, 4,5-epoxypentyl (meth)acrylate, 6,7-epoxypentyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, 4-hydroxybutyl acrylate glycidyl ether, and lactone-modified 3,4-epoxycyclohexyl (meth)acrylate.
[0051] Examples of the (meth)acrylic monomer having a carboxy group include (meth)acrylic acid, acrylic acid dimer, itaconic acid, maleic acid, fumaric acid, crotonic acid, α-(hydroxymethyl)(meth)acrylic acid, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxypropyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxypropyl hexahydrophthalate, β-carboxyethyl (meth)acrylate, ethylene oxide-modified succinic acid (meth)acrylate, ω-carboxypolycaprolactone (meth)acrylate, and p-vinylbenzoic acid.
[0052] Examples of the (meth)acrylate monomer having an isocyanato group and its blocked monomer include (meth)acryloyl isocyanate, 2-isocyanatoethyl (meth)acrylate, 2-(meth)acryloyloxyethoxyethyl isocyanate, 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate, m-(meth)acryloylphenyl isocyanate, and α,α-dimethyl-4-isopropenylbenzyl isocyanate.
[0053] [Content of (meth)acrylic monomer (b2) having a crosslinkable group] The content of the (meth)acrylic monomer (b2) having a crosslinkable group is preferably in the range of 5 to 35 mass% based on the total mass of the monomers constituting the (meth)acrylic unit (B). When the content of the (meth)acrylic monomer (b2) having a crosslinkable group is 5 to 35 mass%, the unevenness covering property and the flexibility and heat resistance of the cured film are excellent.
[0054] [Other monomers] The other monomers other than the monomers (b1) and (b2) used for forming the (meth)acrylic unit (B) are not particularly limited as long as they are copolymerizable with the monomers (b1) and (b2), and can be appropriately selected from known ethylenically unsaturated monomers. Examples of such other ethylenically unsaturated monomers include linear or branched alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tertiary butyl (meth)acrylate, isoamyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, and isomyristyl (meth)acrylate; cyclohexyl (meth)acrylate, tertiary butyl cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and dicyclopentanyl oxy (meth)acrylate. Cyclic alkyl (meth)acrylates such as diethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and isobornyl (meth)acrylate; fluoroalkyl (meth)acrylates such as trifluoroethyl (meth)acrylate, octafluoropentyl (meth)acrylate, perfluorooctylethyl (meth)acrylate, and tetrafluoropropyl (meth)acrylate; (meth)acrylates having a heterocyclic ring such as tetrahydrofurfuryl (meth)acrylate and 3-methyl-3-oxetanyl (meth)acrylate; (meth)acrylates having an aromatic ring such as benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, and nonylphenoxypolyethylene glycol (meth)acrylate;Methoxy polyethylene glycol mono(meth)acrylate, octoxy polyethylene glycol polypropylene glycol mono(meth)acrylate, lauroxy polyethylene glycol mono(meth)acrylate, phenoxy polyethylene glycol mono(meth)acrylate, phenoxy polyethylene glycol polypropylene glycol mono(meth)acrylate, polyethylene glycol monomethyl ether (meth)acrylate, lauroxy polyethylene glycol mono(meth)acrylate, nonylphenoxy polyethylene glycol mono(meth)acrylate, nonylphenoxy polypropylene glycol mono(meth)acrylate, nonylphenoxy polyethylene glycol polypropylene glycol mono(meth)acrylate, phenoxy polyethylene glycol mono(meth)acrylate, methoxy polyethylene glycol (meth)acrylate, n-butoxyethyl (meth)acrylate, n-butoxydiethylene glycol (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate and other alkyl ether group-containing (meth)acrylates; styrene, α-methylstyrene, vinyl acetate and other vinyls;(Meth)acrylamide, N-methyl (meth)acrylamide, N-butyl (meth)acrylamide, diacetone (meth)acrylamide, N-methoxymethyl-(meth)acrylamide, N-ethoxymethyl-(meth)acrylamide, N-propoxymethyl-(meth)acrylamide, N-butoxymethyl-(meth)acrylamide, N-pentoxymethyl-(meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-dibenzyl (meth)acrylamide, methacrylformamide, N-methyl N-vinylacetamide, N-vinylpyrrolidone, N,N-di(methoxymethyl)acrylamide, N-ethoxymethyl-N-methyl Examples of the (meth)acrylates having a nitrogen atom include N,N-di(ethoxymethyl)(meth)acrylamide, N-ethoxymethyl-N-propoxymethyl(meth)acrylamide, N,N-di(propoxymethyl)(meth)acrylamide, N-butoxymethyl-N-(propoxymethyl)(meth)acrylamide, N,N-di(butoxymethyl)(meth)acrylamide, N-butoxymethyl-N-(methoxymethyl)(meth)acrylamide, N,N-di(pentoxymethyl)(meth)acrylamide, N-methoxymethyl-N-(pentoxymethyl)(meth)acrylamide, and cinnamic acid amide. These may be used alone or in combination of two or more.
[0055] [Polymerization initiator] As the polymerization initiator, known azo compounds and organic peroxides can be used. Examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), dimethyl 1,1'-azobis(1-cyclohexanecarboxylate), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]. Examples of organic peroxides include benzoyl peroxide, t-butyl peroxy 2-ethylhexaate, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxyneodecanoate, t-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide. These may be used alone or in combination of two or more.
[0056] The amount of the polymerization initiator used is preferably 0.001 to 15% by mass based on the total mass of the ethylenically unsaturated monomers forming the (meth)acrylic unit (B). A range of 0.001 to 15% by mass is preferable because chain transfer polymerization proceeds effectively.
[0057] [Weight average molecular weight of (meth)acrylic unit (B)] The weight average molecular weight of the (meth)acrylic unit (B) is not particularly limited, and is preferably from 2,000 to 200,000. If it is 2,000 or more, the unevenness covering ability is excellent, and if it is 200,000 or less, viscosity adjustment is easy.
[0058] [Weight average molecular weight of urethane-acrylic composite resin] The weight average molecular weight of the urethane-acrylic composite resin is not particularly limited, but is preferably in the range of 5,000 to 300,000, and more preferably in the range of 10,000 to 100,000. If it is 5,000 or more, it has excellent unevenness covering ability, and if it is 300,000 or less, it is easy to adjust the viscosity.
[0059] <Solvent> The reaction for producing the urethane-acrylic composite resin may be carried out using a solvent. These solvents may be used alone or in combination of two or more. The solvent that may be used in the reaction of the polyol with the polyisocyanate is not particularly limited as long as it does not react with an isocyanato group, and examples thereof include acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, ethyl acetate, propyl acetate, toluene, xylene, anisole, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, N-vinylpyrrolidone, N-methylcaprolactam, dimethylsulfoxide, tetramethylurea, pyridine, dimethylsulfone, hexamethylsulfoxide, m-cresol, γ-butyrolactone, and γ-valerolactone. As the solvent that may be used in the reaction between the urethane prepolymer and the chain transfer agent, in addition to the above-mentioned solvents, alcohols such as ethanol, isopropanol, tertiary butanol, and diacetone alcohol can be used.
[0060] <Crosslinking agent> The resin sheet of the present invention is formed from a resin composition containing the above-mentioned urethane-acrylic composite resin and a crosslinking agent. The crosslinking group derived from the (meth)acrylic monomer (b2) reacts with the crosslinking agent to cure, thereby obtaining a cured product having excellent flexibility and heat resistance. The crosslinking agent is not particularly limited as long as it has a functional group capable of reacting with the crosslinkable group in the molecule, and examples of such functional groups include an epoxy group, an acid anhydride group, a phenol group, an isocyanato group and its block, an amino group, a hydroxyl group, and a carboxy group. The crosslinking agent may be used alone or in combination of two or more.
[0061] Examples of crosslinking agents having an epoxy group include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidylaniline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidylaminophenylmethane, triglycidyl isocyanurate, and triglycidyl-p-aminophenol.
[0062] Examples of crosslinking agents having an acid anhydride group include phthalic anhydride, trimellitic anhydride, and maleic anhydride.
[0063] The crosslinking agent having a phenol group may be a monomer compound or a polymer compound. The crosslinking agent having a phenol group, which is a polymer compound, may be a polymer (homopolymer) of a single monomer or a copolymer (copolymer) of multiple types of monomers. The crosslinking agent having a phenol group may be any of a random copolymer, a block copolymer, or a graft copolymer. Examples of crosslinking agents having a phenol group include bisphenol A, bisphenol F, bisphenol S, resorcin, catechol, hydroquinone, fluorene bisphenol, 4,4'-biphenol, 4,4',4"-trihydroxytriphenylmethane, naphthalene diol, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, calixarene, novolac-type phenolic resins (e.g., polyhydric phenol novolac resins synthesized from polyhydric hydroxy compounds and formaldehyde, such as phenol novolac resins, cresol novolac resins, bisphenol A novolac resins, bisphenol S novolac resins, and resorcin novolac resins), naphthol-phenol co-condensed novolac resins, naphthol-cresol co-condensed novolac resins, naphthol novolac resins, and alco Examples of polyhydric phenol compounds include polyhydric phenol compounds such as alkoxy group-containing aromatic ring-modified novolak resins (polyhydric phenol compounds in which a phenol nucleus and an alkoxy group-containing aromatic ring are linked by formaldehyde)), aralkyl-type phenol resins (for example, phenol aralkyl resins and naphthol aralkyl resins such as Xylok resin), aromatic hydrocarbon formaldehyde resin-modified phenol resins, dicyclopentadiene phenol addition type resins, trimethylolmethane resins, tetraphenylolethane resins, biphenyl-modified phenol resins (polyhydric phenol compounds in which a phenol nucleus is linked by a bismethylene group), biphenyl-modified naphthol resins (polyhydric naphthol compounds in which a phenol nucleus is linked by a bismethylene group), and aminotriazine-modified phenol resins (polyhydric phenol compounds in which a phenol nucleus is linked by melamine, benzoguanamine, or the like).
[0064] As the crosslinking agent having an isocyanato group, for example, the description in the above [Polyisocyanate] can be used. In addition, as the crosslinking agent having an isocyanato group, a biuret, a nurate, an adduct, or other condensation product of the above polyisocyanate may be used. An example of the biuret is a biuret of hexamethylene diisocyanate. Examples of the nurate form include a nurate form of hexamethylene diisocyanate, a nurate form of isophorone diisocyanate, and a nurate form of tolylene diisocyanate. Examples of the adduct include an adduct of trimethylolpropane with hexamethylene diisocyanate, an adduct of trimethylolpropane with isophorone diisocyanate, and an adduct of toluene diisocyanate. Other condensates include polyfunctional compounds having an isocyanato group, carbodiimide-modified compounds, biuret-modified compounds, and allophanate-modified compounds, such as polymethylene polyphenyl polyisocyanate, a biuret compound of hexamethylene diisocyanate, and carbodiimide-modified diphenylmethane diisocyanate.
[0065] Examples of the crosslinking agent having a blocked isocyanato group include the above-mentioned crosslinking agent having an isocyanato group blocked with a known blocking agent, such as phenols, alkylphenols, active methylene compounds, oximes, lactams, bisulfites, and imidazoles.
[0066] Examples of crosslinking agents having an amino group include the above-mentioned aliphatic amine compounds and aromatic amine compounds, as well as bifunctional or higher polyether amines such as JEFFAMINE D-230, D-400, D-2000, T-403, and T-3000 (all manufactured by HUNTSMAN).
[0067] As the crosslinking agent having a hydroxyl group, for example, the description of the "low molecular weight polyol" in the above section (Polyether polyol) can be used.
[0068] Examples of crosslinking agents having a carboxy group include succinic acid, adipic acid, sebacic acid, maleic acid, phthalic acid, naphthalene dicarboxylic acid, methylphthalic acid, cyclohexane dicarboxylic acid, methylcyclohexane dicarboxylic acid, methylnorbornene dicarboxylic acid, tetrahydrophthalic acid, trimellitic acid, trimesic acid, pyromellitic acid, and naphthalene tetracarboxylic acid.
[0069] The molar ratio of the functional group in the crosslinking agent to the crosslinkable group in the urethane-acrylic composite resin (the number of moles of the functional group in the crosslinking agent / the number of moles of the crosslinkable group in the urethane-acrylic composite resin) is preferably 0.2 to 10.0, more preferably 0.5 to 5.0. A molar ratio of 0.2 to 10.0 is preferable because it provides excellent flexibility.
[0070] <Resin sheet> The resin sheet of the present invention can be obtained by molding the above-mentioned resin composition into a sheet. The method for producing the resin sheet is not particularly limited, and for example, the resin sheet can be produced by uniformly stirring and mixing a urethane-acrylic composite resin, a crosslinking agent, and a solvent to obtain a resin composition, applying the resin composition onto a release film using a doctor blade or the like, drying the resin composition in an oven, and then cooling the resin composition to room temperature to solidify the resin sheet. The oven temperature is usually in the range of 60°C to 100°C, and the thickness of the resin sheet is preferably 100 μm to 3 mm.
[0071] [Filler] The resin sheet of the present invention may contain a filler within a range that does not impair the effects of the present invention. Examples of the filler include colorants such as titanium oxide and carbon black; metal powders such as ferrite; inorganic fibers such as glass fibers and metal fibers; organic fibers such as carbon fibers and aramid fibers; heat-conducting agents such as aluminum nitride, boron nitride, aluminum hydroxide, alumina, magnesium oxide, carbon nanotubes, and expanded graphite; inorganic whiskers such as glass beads, glass balloons, glass flakes, glass fibers, calcium carbonate, magnesium carbonate, potassium titanate whiskers, and zinc oxide whiskers; and fillers such as talc, silica, calcium silicate, kaolin, diatomaceous earth, montmorillonite, graphite, pumice, ebonized powder, cotton flock, cork powder, barium sulfate, and fluororesin. The filler may be used alone or in combination of two or more types.
[0072] The resin sheet of the present invention may further contain known additives such as a curing accelerator, an antiaging agent, an antioxidant, an antistatic agent, a weather resistance agent, an ultraviolet absorber, an antiblocking agent, a crystal nucleating agent, a flame retardant, a vulcanizing agent, a vulcanization aid, an antibacterial / antifungal agent, a dispersing agent, a coloring inhibitor, a foaming agent, and a rust inhibitor, provided that the effects of the present invention are not impaired.
[0073] By using the resin sheet of the present invention, for example, electronic devices can be sealed as follows. First, the resin sheet is laminated on an electronic circuit board and heated in an atmosphere of 60°C to 100°C for 30 to 60 seconds. Here, it immediately softens and easily conforms to the unevenness of the electronic components under its own weight to form a coating film. Next, it is heated in an atmosphere of 80°C to 120°C for 10 to 60 minutes, hardened, and sealed. However, the method for sealing an electronic circuit board with the resin sheet of the present invention is not limited to the above.
[0074] The resin sheet of the present invention can greatly simplify the sealing process and can seal at a low temperature, so it can be applied to electronic circuit boards with low heat resistance. In addition, it has excellent flexibility and heat resistance, and is suitable for protecting various electronic circuit boards, i.e., various boards such as rigid boards and FPC boards. EXAMPLES
[0075] The present invention will be described in more detail below with reference to examples, but the following examples are not intended to limit the scope of the invention. In the examples, "parts" and "%" represent "parts by mass" and "% by mass", respectively, unless otherwise specified.
[0076] <Weight average molecular weight (Mw)> The weight average molecular weight (Mw) of the resin was determined by gel permeation chromatography (GPC) using a polystyrene standard as a conversion value. The measurement was performed using a GPC-8020 (Tosoh Corporation) as a GPC device, tetrahydrofuran as an eluent, and three TSKgel SuperHM-M (Tosoh Corporation) columns connected in series under the conditions of a flow rate of 0.6 ml / min, an injection volume of 10 μl, and a column temperature of 40°C.
[0077] <Solid content concentration> The solid content concentration of the resin was measured in accordance with JIS K5601-1-2 at a heating temperature of 150° C. for a heating time of 20 minutes, and the heating residue was used.
[0078] The abbreviations for compounds used in this specification are shown below. <Polyol> T-5651: Bifunctional polycarbonate polyol, number average molecular weight 1,000, hydroxyl value 113 mgKOH / g, product name "Duranol T5651", manufactured by Asahi Kasei Corporation PTG-1000SN: Bifunctional polytetramethylene ether glycol, number average molecular weight 1,000, hydroxyl value 112 mgKOH / g, manufactured by Hodogaya Chemical Co., Ltd. 112mgKOH / g, manufactured by Adeka Corporation <Polyisocyanate> IPDI: Isophorone diisocyanate
[0079] <(Meth)acrylic monomer> SA: Stearyl acrylate SMA: Stearyl methacrylate ·VA: Behenyl acrylate ·AA: Acrylic acid HEMA: 2-hydroxyethyl methacrylate BMA: Butyl methacrylate
[0080] <Crosslinking agent> jER630: p-aminophenol type liquid epoxy resin, product name "jER630", manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 94.3g / eq BL3370: Aliphatic blocked isocyanate, product name "Desmodur BL3370", manufactured by Sumika Bayer Urethane Co., Ltd., solids concentration 70%, NCO content 8.9%
[0081] <Catalyst> C11Z-CN: 1-cyanoethyl-2-undecylimidazole, product name "Curesol C11Z-CN", manufactured by Shikoku Chemical Industry Co., Ltd. ·DBTDL: Dibutyltin dilaurate
[0082] <Production of urethane-acrylic composite resin> (Production Example 1) A reaction vessel equipped with a nitrogen gas inlet tube, a stirrer, a thermometer, and a reflux condenser was charged with 74.9 parts of T-5651 as a polyol, 25.1 parts of isophorone diisocyanate as a polyisocyanate, and 0.01 parts of dibutyltin dilaurate as a catalyst, and after uniform stirring, the mixture was reacted at 90°C for 5 hours under a nitrogen atmosphere to obtain a urethane prepolymer. The mixture was then cooled to 80°C, and 11.0 parts of methyl ethyl ketone as a solvent, 31.7 parts of toluene, and 5.5 parts of 2-aminoethanethiol as a chain transfer agent were added, followed by reaction at 75°C for 2 hours to obtain a urethane unit. The end point of the reaction was determined by FT-IR, when a peak derived from an isocyanato group (2270cm) was detected. -1 This was confirmed by the disappearance of the nearby Next, 135.4 parts of SA as a crystalline (meth)acrylic monomer (b1), 12.3 parts of AA as a (meth)acrylic monomer (b2) having a crosslinkable group, 98.5 parts of BMA as other ethylenically unsaturated monomers, and toluene were added so that the ratio of the solvent in the reaction vessel was 40%, and after uniform stirring, the temperature was raised to 75°C under a nitrogen atmosphere. 0.08 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added as a polymerization initiator in 13 divided portions every 30 minutes, and the reaction was continued for another 2 hours after the addition of the polymerization initiator to form a (meth)acrylic unit. Toluene was added to adjust the solid concentration to 60%, and a urethane-acrylic composite resin solution of Production Example 1 was obtained.
[0083] (Production Examples 2 to 15, Comparative Production Examples 1 to 2) The same procedure as in Production Example 1 was carried out except that the compounds and blending compositions were changed to those shown in Table 1, to obtain urethane-acrylic composite resin solutions of Production Examples 2 to 15 and Comparative Production Examples 1 and 2, respectively.
[0084] Table 1 shows the weight-average molecular weight of the obtained urethane-acrylic composite resin, the content (%) of urethane unit (A) in the urethane-acrylic composite resin, the content (%) of crystalline (meth)acrylic monomer (b1) in the (meth)acrylic unit (B), and the content (b2) of (meth)acrylic monomer having a crosslinkable group in the (meth)acrylic unit (B).
[0085] [Table 1]
[0086] (Comparative Manufacturing Example 3) Urethane resin In a reaction vessel equipped with a nitrogen gas inlet tube, a stirrer, a thermometer, and a reflux condenser, 100.0 parts of T-5651 as a polyol, 14.9 parts of isophorone diisocyanate as a polyisocyanate, and 0.01 parts of dibutyltin dilaurate as a catalyst were charged, and after uniform stirring, the mixture was reacted at 90°C for 5 hours under a nitrogen atmosphere, and 76.6 parts of toluene were added to obtain a comparative urethane resin solution. The weight average molecular weight of the obtained urethane resin was 8,300, and the solid content concentration was 60%.
[0087] (Comparative Manufacturing Example 4) Acrylic Resin In a reaction vessel equipped with a nitrogen gas inlet tube, a stirrer, a thermometer, and a reflux condenser, 137.3 parts of SA, 19.6 parts of AA, 39.2 parts of n-butyl methacrylate, 7.3 parts of 2-ethylhexyl thioglycolate, and 136.0 parts of toluene were added and stirred uniformly, and then heated to 75°C under a nitrogen atmosphere. 0.1 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added as a polymerization initiator in 13 separate portions every 30 minutes, and after all of the polymerization initiator was added, the reaction was continued for another 2 hours to obtain an acrylic resin solution for comparison. The weight average molecular weight of the obtained acrylic resin was 8,900, and the solid content concentration was 60%.
[0088] (Comparative Manufacturing Example 5) 20 parts of DER383J (bisphenol A type epoxy resin, epoxy equivalent 190 g / eq, manufactured by Dow Chemical Co.), 80 parts of NC3300 (biphenyl skeleton-containing multifunctional epoxy resin, epoxy equivalent 285 g / eq, manufactured by Nippon Kayaku Co., Ltd.), 4 parts of dicyandiamide, 4 parts of U-CAT3502T (aromatic dimethylurea, manufactured by San-Apro Co., Ltd.), 300 parts of FB-959 (spherical silica, particle size 25 μm, manufactured by Denki Kagaku Kogyo Co., Ltd.), and 20 parts of H42M (aluminum hydroxide (particle size 1.5 μm, manufactured by Showa Denko Co., Ltd.) were charged into a kneader and mixed with stirring at 75 ° C. for 1 hour to obtain a comparative resin composition.
[0089] (Comparative Manufacturing Example 6) 15 parts of DER383J (bisphenol A type epoxy resin, epoxy equivalent 190 g / eq, manufactured by Dow Chemical Co.), 85 parts of NC3300 (biphenyl skeleton-containing multifunctional epoxy resin, epoxy equivalent 285 g / eq, manufactured by Nippon Kayaku Co., Ltd.), 4 parts of dicyandiamide, 4 parts of U-CAT3502T (aromatic dimethylurea, manufactured by San-Apro Co., Ltd.), 10 parts of FB-959 (spherical silica, particle size 25 μm, manufactured by Denki Kagaku Kogyo Co., Ltd.), and 20 parts of H42M (aluminum hydroxide (particle size 1.5 μm, manufactured by Showa Denko Co., Ltd.) were charged into a kneader and mixed with stirring at 75 ° C. for 1 hour to obtain a comparative resin composition.
[0090] <Preparation of resin sheet> [Example 1] 10.0 parts of the urethane-acrylic composite resin solution obtained in Production Example 1, 0.3 parts of jER630 as a crosslinking agent, 0.1 parts of C11Z-CN as a catalyst, and 2.4 parts of tetrahydrofuran were mixed and stirred uniformly at room temperature to obtain a resin composition. The obtained resin composition was applied onto a release film so that the thickness after drying would be 300 μm, and dried in a hot oven at 80°C for 5 minutes. After cooling, the release film was removed to prepare a resin sheet.
[0091] [Examples 2 to 15 and Comparative Examples 1 to 5] Resin sheets of Examples 2 to 15 and Comparative Examples 1 to 5 were produced in the same manner as in Example 1, except that the blending composition was changed to that shown in Table 2. Note that the resin sheet of Comparative Example 1 had high viscosity, and it was difficult to remove the release film, so that a resin sheet could not be produced.
[0092] [Comparative Examples 6 to 7] Resin sheets of Comparative Examples 6 and 7 were produced in the same manner as in Example 1, except that the resin composition was changed as shown in Table 2.
[0093] <Evaluation of resin sheets> The following tests were carried out on the obtained resin sheet. The results are shown in Table 2. For Comparative Example 1 in which a resin sheet could not be produced, the following evaluations were not carried out.
[0094] [Coating] A chip measuring 10 mm in length, 10 mm in width, and 2 mm in thickness was mounted on an FR-4 board. A resin sheet cut to 20 mm in length and 20 mm in width was placed on top of the chip and softened in a heated oven at 80°C for one minute. The coverage of the chip's convex corners and the coverage of the contact points between the chip side and the board were evaluated and rated according to the following criteria.
[0095] (Evaluation criteria for coverage of convex corners) ○: The thickness of the coating is 20 μm or more (good) △: The thickness of the coating is less than 20 μm, but there is no exposed tip (usable). ×: The tip is exposed in places (unusable)
[0096] (Evaluation criteria for contact coverage) ○: The contact area is completely covered with the resin sheet (good) △: There is a slight gap between the resin sheet (usable) ×: There is a gap between the resin sheet (not suitable for use)
[0097] [Flexibility] The resin sheet was cut into 5 mm-wide strips to prepare test pieces for evaluation. Using these test pieces, a tensile test was performed at a tensile speed of 50 mm / min to measure the breaking elongation (%) and evaluate it according to the following criteria.
[0098] (Flexibility evaluation criteria) ○: Breaking elongation is 100% or more (good) △: Breaking elongation is 50% or more and less than 100% (usable) ×: Breaking elongation is less than 50% (unusable)
[0099] [Heat resistance] After the above-mentioned coating evaluation, the test piece was left to stand in an environment of 120°C for 500 hours, and then the coating thickness of the convex corner was evaluated. The thickness change before and after the heat resistance test was judged according to the following criteria. Note that the heat resistance evaluation was not carried out for those in which the coating property of the convex corner before the heat resistance test was judged as ×.
[0100] (Evaluation criteria for heat resistance) ○: Thickness change rate is less than 20% (good) △: Thickness change rate is 20% or more and less than 35% (usable) ×: Thickness change rate is 35% or more (not suitable for use)
[0101] [Table 2]
[0102] The resin sheet of the present invention exhibited good results in terms of coverage, flexibility, and heat resistance. On the other hand, the adhesive of the comparative example exhibited results inferior to those of the examples in some or all of the coverage, flexibility, and heat resistance.
Claims
1. A resin sheet formed from a resin composition containing a urethane-acrylic composite resin and a crosslinking agent, the urethane-acrylic composite resin is a resin in which a urethane unit (A) and a (meth)acrylic unit (B) are linked together via a chain transfer agent residue, the (meth)acrylic unit (B) has a structural unit derived from a crystalline (meth)acrylic monomer (b1) and a structural unit derived from a (meth)acrylic monomer (b2) having a crosslinkable group (excluding the structural unit derived from (b1)); the crystalline (meth)acrylic monomer (b1) is a (meth)acrylate having a linear alkyl group having 16 or more carbon atoms, A resin sheet, wherein the chain transfer agent residue is derived from a compound having one amino group and one sulfanyl group in the molecule.
2. The resin sheet according to claim 1, wherein the urethane-acrylic composite resin contains the urethane unit (A) in a range of 30 to 70 mass% based on the mass of the urethane-acrylic composite resin.
3. The resin sheet according to claim 1 or 2, which is used for sealing an electronic device.
4. A laminate comprising the resin sheet according to any one of claims 1 to 3 and a release material.
Citation Information
Patent Citations
Acrylic / Urethane copolymer, its production and one-and two-pack coating compositions containing the same
JP1997025324A
Aqueous emulsion, preparation thereof and aqueous coating using the same
JP1999269247A
Aqueous emulsion and water-based coating material prepared therefrom
JP2000178338A
Sheet-like resin composition and circuit component sealed by using the same
JP2011246596A
Sealing method of electronic component
JP2012054363A